Comparative study of permeability in sandstones and shales-using mercury injection capillary pressure (MICP) technique - Ahmad, M. (Asian Research Publishing Network, 2019)
The various types of pores distributions and pore throats in shale and sandstone samples could be easily investigated and evaluated by Mercury Injection Capillary Pressure (MICP) techniques. The focus of this research was to figure out the pore size distribution, particularly in correlation with permeability, from MICP measurements. In this project, the rock samples were taken from Sarawak Basin in Malaysia, in the form of chips. In general, MICP profiling is very dependent on simple size due to both conformance and accessibility of pores. Due to conformance, a correction approach was applied in which we considered the samples' pore volume compression before it was intruded into samples. Mercury injection is used to help in determining the numerous properties of tight shale storage, because there are instances where cuttings from a drilled formation may be limited, and the source rock needed may not be available to be evaluated unless a whole core is taken. Core profiles and cuttings may seem like more plausible choices in calibrating well logs. The distribution of pores and their identification in a single sample may provide the required information on the permeability, porosity and bulk volume of the formation. It could be seen in the results that MICP is highly applicable to capture and figure out the pores size distribution and density in a shale and sandstone sample. From that point of view, the transportation of the gas from the source rock, through the fractures flow paths, into production wells could be understood. Therefore, MICP is a recommended method in analyzing the formation's permeability via its pore size distribution. However, the objective of this study could not be fully envisaged as it has been observed that there are several limitations when it comes to studying shale gas, and these limitations are not only from the unavailability of equipment but also the problem about the number of samples available. Â© 2006-2019 Asian Research Publishing Network (ARPN).